ANALISIS KORELASI KANONIK PADA PERILAKU KESEHATAN DAN KARAKTERISTIK SOSIAL EKONOMI DI KOTA PATI JAWA TENGAH - Safitri, Diah; Indrasari, Paramita (MEDIA STATISTIKA, 2009)
One of the general problem that is social and economics which not yet flatten and still meeting of low health case. To know the correlation between social and economics characteristic and behavior of health in Pati of Central Java is used the canonical correlation analysis. The variable that is taken are  social and economics characteristic and behavior of health variable, which each  consisting of nine indicator variable. Some assumptions like linearity, normal multivariable and do not multicolinearity should be fulfilled. After the assumption have fulfilled, data processing can be done so that obtained a conclusion. The result of canonical correlation analysis indicate that there is a signifikan correlation between social and economics characteristic variable and behavior of health variable. From nine indicator which forming variable of social and economics characteristic, earnings indicator variable, education of mother, expenditure and education of father giving the most dominant of contribution. While from nine behavior of health variable, indicator of balanced nutrient variable, physical activity, eradication of mosquito den, house floor, exclusive ASI, and brush teeth giving the most dominant of contribution.   Keywords   :     Social and Economics Characteristic, Behavioral of Health, Canonical Correlation Analysis